When benign mimics malignancy: giant hypervascular focal nodular hyperplasia requiring left hemi-hepatectomy - R., Obuhovich A.; Amry, M. A. Mohammed; D. K. N. Direcksze, Naveen; Dineshkumar, Prithvi A.; Hasnaa, M. A. Fathima (International Surgery Journal, 2026)
Focal nodular hyperplasia of the liver (FNHL) is a benign, non-invasive, and common liver cell tumor with a habitually lazy course of action. The probability of FNHL transforming into malignancy is very unlikely. The prevalence of FNHL globally is reported as 0.4-3% in the general population and the risk of acquiring FNHL increases with age. A 29-year-old woman presented to the hepatobiliary department of the Grodno University Clinic with complaints of intermittent epigastric pain, early satiety and abdominal bloating. No associated fever, jaundice, weight loss, or gastrointestinal bleeding was present. The patient’s medical history was not significant, and she had no family history of cancer. A large, well-circumscribed heterogeneous lesion occupying the left lobe of the liver was demonstrated on the abdominal ultrasound scan. Contrast enhanced computed tomography (CT) revealed a giant hypervascular mass with intense arterial phase enhancement and partial washout during the portal venous phase. Furthermore, magnetic resonance imaging further confirmed a hypervascular lesion arising predominantly from segments II, III, and IV of the liver. This case report illustrates the diagnostic challenges aroused by giant hypervascular focal nodular hyperplasia (FNH), a benign liver lesion that can precisely replicate the characteristic features of malignant tumors, both clinically and radiologically.